Civically Engaged and Inclusive Pedagogy: Facilitating a multidisciplinary course on human trafficking - Alejano-Steele, Annjanette Ramiro (Anti-Trafficking Review, 2021)
For university instructors who teach human trafficking as a comprehensive course, design decisions often begin with determining scope, disciplinary orientation, and learning goals. Further decisions involve pedagogical approaches and how to best support and sustain student learning. With civic engagement principles, universities can situate themselves within local anti-trafficking initiatives by offering courses to expand organisational capacities to end human trafficking. Using Human Trafficking 4160 at Metropolitan State University of Denver as an example, this paper provides key design questions to create a civically-engaged multidisciplinary course, partnered with agencies statewide, and equipped to support students primed for social justice and systems change. It offers suggestions for community partnerships to deliver content and co-create learning activities. It also provides pedagogical techniques to facilitate inclusive, trauma-informed learning spaces.